Molecular basis for the disease-modifying effects of belimumab in systemic lupus erythematosus and molecular predictors of early response: blood transcriptome analysis implicates the innate immunity and DNA damage response pathways - Moysidou, Georgia Savina; Garantziotis, Panagiotis; Sentis, George; Nikoleri, Dimitra; Malissovas, Nikolaos; Nikoloudaki, Myrto; Stergioti, Eirini Maria; Polia, Styliani; Paschalidis, Nikolaos; Filia, Anastasia; Grigoriou, Maria; Nikolopoulos, Dionysis; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives Belimumab is a putative disease-modifying agent in systemic lupus erythematosus (SLE), yet the molecular underpinnings of its effects and the ability to predict early clinical response remain unexplored. To address these, we undertook a longitudinal, in-depth blood transcriptome study. Methods RNA-sequencing was performed in the blood of active SLE patients at baseline and following 6 months of belimumab treatment (n=45 paired samples). Clinical response was determined according to the SLE Responder Index (SRI)-4 and Lupus Low Disease Activity State (LLDAS). Weighted correlation network analysis (WGCNA) was used to uncover gene module trait associations. Reversibility of SLE susceptibility and severity gene signatures was assessed. Machine learning was used to build models predictive of response. results Belimumab induced widespread transcriptome changes with downregulation of pathways related to B cells, type I/II interferon, IL-6/STAT3 and neutrophil activation. These effects were more pronounced among patients with LLDAS+ compared with to SRI-4+/LLDAS–response, with amelioration of the SLE’susceptibility’ signature observed in the former group. Unsupervised analysis unveiled gene modules enriched in neutrophil degranulation, type I interferon signalling and cytokine production to correlate positively with response at 6 months. Using neural networks, a set of 50 genes (including CCL4L2, CARD10, MMP15 and KLRC2) predicted response to belimumab with a cross-validated 84% specificity (test set). Lack of response was linked to perturbations of the cell cycle checkpoints, PI3K/Akt/mammalian target of rapamycin and TGF-beta signalling pathways. Conclusion Belimumab treatment ameliorates multiple innate and adaptive immunity dysregulations of SLE and may reverse the disease signature, consistent with the drug effects on reducing activity and preventing flares. Fingerprints of innate immunity correlate with robust improvement whereas DNA damage response with less responsive disease to BAFF inhibition.
CRIS-Team Scopus Importer:2025-02-04